Perspektif Cendekiawan Buddhis Indonesia tentang Mediokritas Peran Mahasiswa Perguruan Tinggi Keagamaan Buddha sebagai Agent Of Change - Karniawan, Arya Whisnu; Isomudin, Isomudin; Dharmika, Ida Bagus; Sugiyarti, Ririn; Linawati, Linawati (LPPPI Publishing, 2022)
Development of technology in various fields is increasing rapidly. Younger generation will face competition from two things, namely competition between individuals and competition with robots/AI. Unfortunately, many of Indonesia's young generation adhere to the mindset of